2023
DOI: 10.1021/acsami.2c17523
|View full text |Cite
|
Sign up to set email alerts
|

Oxidatively Doped Tetrathiafulvalene-Based Metal–Organic Frameworks for High Specific Energy of Supercapatteries

Abstract: Poor electrical conductivity and instability of metal–organic frameworks (MOFs) have limited their energy storage and conversion efficiency. In this work, we report the application of oxidatively doped tetrathiafulvalene (TTF)-based MOFs for high-performance electrodes in supercapatteries. Two isostructural MOFs, formulated as [M(py-TTF-py)(BPDC)]·2H2O (M = NiII (1), ZnII (2); py-TTF-py = 2,6-bis(4′-pyridyl)TTF; H2BPDC = biphenyl-4,4′-dicarboxylic acid), are crystallographically characterized. The structural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…By fitting the curves, the charge transfer impedances before and after 500, 1000, and 1500 cycles are 11.91, 12.53, 12.77, and 12.96 Ω, respectively, further verifying the cycle stability. We once reported that two TTF-MOFbased supercapacity cells can power a "TTF-MOF" pattern constructed by 41 red light-emitting diode (LED) lights and maintain the light on for ∼300 s. 43 Now, one 1||AC HLIC full cell can maintain the light on for ∼480 s (inset in Figure 6d and Video S2), demonstrating its prospects in energy-storage devices.…”
mentioning
confidence: 99%
“…By fitting the curves, the charge transfer impedances before and after 500, 1000, and 1500 cycles are 11.91, 12.53, 12.77, and 12.96 Ω, respectively, further verifying the cycle stability. We once reported that two TTF-MOFbased supercapacity cells can power a "TTF-MOF" pattern constructed by 41 red light-emitting diode (LED) lights and maintain the light on for ∼300 s. 43 Now, one 1||AC HLIC full cell can maintain the light on for ∼480 s (inset in Figure 6d and Video S2), demonstrating its prospects in energy-storage devices.…”
mentioning
confidence: 99%